2014
DOI: 10.1108/imds-03-2014-0076
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organisation culture on E-commerce adoption

Abstract: Purpose-The purpose of this paper is to empirically examine the influence of different organisational cultures on e-commerce adoption maturity in small-and medium-sized enterprises (SMEs). Design/methodology/approach-The data for this study were gathered using postal survey questionnaire and analysed using quantitative analysis methods. Findings-The result indicates a positive correlation between adhocracy culture and e commerce adoption. However, those firms with hierarchy cultural characteristics indicate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
2
27
0
2
Order By: Relevance
“…Organizations differ in their deployment of e-commerce and it is necessary to examine factors that influence the implementation of e-commerce (EC) technologies as this can help the organization to appropriately design and control adoption of e-commerce. By examining the influence of e-commerce adoption in Jordan commercial banks, this study has bridged the gap to help decision makers realize the importance of organization culture and its effect on implementing e-commerce (Senarathna et al, 2014 According to the researchers' knowledge, this study might be the first of its kind in Jordan to examine the influence of organizational culture on the adoption of e-commerce in Jordanian commercial banks. This study highlights the importance of the internal structure of the organization and its influence on e-commerce adoption.…”
Section: Importance Of the Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Organizations differ in their deployment of e-commerce and it is necessary to examine factors that influence the implementation of e-commerce (EC) technologies as this can help the organization to appropriately design and control adoption of e-commerce. By examining the influence of e-commerce adoption in Jordan commercial banks, this study has bridged the gap to help decision makers realize the importance of organization culture and its effect on implementing e-commerce (Senarathna et al, 2014 According to the researchers' knowledge, this study might be the first of its kind in Jordan to examine the influence of organizational culture on the adoption of e-commerce in Jordanian commercial banks. This study highlights the importance of the internal structure of the organization and its influence on e-commerce adoption.…”
Section: Importance Of the Studymentioning
confidence: 99%
“…Conclusions considering the influence of an adhocracy culture type of e-commerce adoption were contradictory and indicated that e-commerce adoption was linked to risk appetite of the organization and that market culture was related to competitive benefits. Senarathna et al (2014) studied the influence of different organizational cultures on e-commerce adoption in SMEs. Data was collected using a portal survey questionnaire and subsequently analyzed using quantitative analysis methods.…”
Section: Adhocracy Culture and E-commercementioning
confidence: 99%
See 3 more Smart Citations